2017
DOI: 10.1101/156570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The eardrums move when the eyes move: A multisensory effect on the mechanics of hearing

Abstract: Interactions between sensory pathways such as the visual and auditory systems are known to occur in the brain, but where they first occur is uncertain. Here, we show a multimodal interaction evident at the eardrum. Ear canal microphone measurements in humans (n = 19 ears in 16 subjects) and monkeys (n = 5 ears in three subjects) performing a saccadic eye movement task to visual targets indicated that the eardrum moves in conjunction with the eye movement. The eardrum motion was oscillatory and began as early a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 72 publications
3
20
1
Order By: Relevance
“…While we did not find that attention changed ear-canal noise through MOC inhibition, we did find 502 that the decrease in ear-canal noise was a very robust indicator of whether subjects were or were not Recently, Gruters et al (2018) found an interaction between saccadic eye movement and changes in 511 ear-canal sound pressure that lasted for 10's of milliseconds. The infrasounds produced by such eye 512 movements would have been filtered out in our measurements, but they do point out that there are 513 many subject motion changes that may affect ear-canal noise.…”
Section: Comparison With Previous Reports 441contrasting
confidence: 61%
“…While we did not find that attention changed ear-canal noise through MOC inhibition, we did find 502 that the decrease in ear-canal noise was a very robust indicator of whether subjects were or were not Recently, Gruters et al (2018) found an interaction between saccadic eye movement and changes in 511 ear-canal sound pressure that lasted for 10's of milliseconds. The infrasounds produced by such eye 512 movements would have been filtered out in our measurements, but they do point out that there are 513 many subject motion changes that may affect ear-canal noise.…”
Section: Comparison With Previous Reports 441contrasting
confidence: 61%
“…Using the three-origin horizontal slice task, we first replicated our original findings by analyzing only the trials that used similar targets as previously published work [30].…”
Section: Resultsmentioning
confidence: 84%
“…Thus, the brain has the opportunity to tailor how ascending sensory signals are first encoded, and potentially adjust ascending auditory signals to facilitate linking to the visual system at later stages. movement-related eardrum oscillations (EMREOs) are a recently discovered phenomenon in which the eardrum oscillates, time-locked to both saccade onset and offset, in the absence of incoming sound [30]. These oscillations likely reflect descending eye movement-related neural commands that influence the ears' internal motor elements -the middle ear muscles, outer hair cells, or some combinationin a still unknown fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Besides anatomical studies, recent magnetoencephalography studies investigating predictions in auditory scenes in humans found significant effective connectivity from motor cortex toward auditory areas (Abbasi and Gross, 2020;Morillon and Baillet, 2017). Additionally, besides direct projections, an indirect source of motor influences on the auditory system could stem from the cochlea, as a recent study reported oscillations of the eardrum coinciding with saccade onset in the absence of sound (Gruters et al, 2018). The authors hypothesized that the eardrum movement is due to a copy of the motor command that generates saccades.…”
Section: The Circuitry Of Saccade Related Entrainment In A1mentioning
confidence: 99%